Dispersion method for hydrophobic nano-silica aerogels in cement-based composites based on reversible regulation - Lu Lu; Haodong Wang; Ming Ye; Jiashun Hu; Shan Yun; Bin Xu; Mingming Wang (Materials & Design)
In the context of carbon neutrality, external wall insulation technology has entered a new developmental phase. Hydrophobicity is an important indicator of the weather resistance of external wall insulation materials. In this study, we successfully developed a method to prepare a hydrophilic silica aerogel paste by mixing hydrophobic nano-silica aerogel powder with an ethanol–water solution, thereby addressing the dispersion challenge in cement-based composites. Upon drying, the aerogel reverts to its hydrophobic state while maintaining its nanoporous structure, representing a mechanism of reversible regulation. The dispersion characteristics of the silica aerogel paste in water were investigated through experiments and numerical simulations. Based on these finding, a preparation method was proposed for silica aerogel cement-based composites. Optical microscopy tests revealed that silica aerogel participated in the cement hydration process and became embedded in the cement material, significantly reducing its thermal conductivity. Energy-dispersive spectroscopy point scanning for carbon element analysis confirmed the effective restoration of methyl groups, confirming the uniform dispersion of the nano-silica aerogel in the cement-based material. This study is of great significance for promoting the application of hydrophobic nano-silica aerogels in the modification of cement-based composite insulation materials. It also provides new insights and methods for technological advancements in relevant fields.